Loop Electrosurgical Excision Procedure Findings for Identification of Patients With Early-Stage Cervical Cancer Suitable for Less Radical Surgery. Issue 7 (1st September 2012) - Kim, Mi-Kyung; Kim, Min A; Kim, Jae Weon; Chung, Hyun Hoon; Park, Noh-Hyun; Song, Yong-Sang; Kang, Soon-Beom
Abstract : Objective: To define a subset of patients with early-stage cervical cancer at low risk for parametrial invasion through pathologic parameters of loop electrosurgical excision procedure (LEEP). Materials and Methods: A retrospective analysis of data from 131 patients who underwent LEEP before radical hysterectomy or radical trachelectomy for stage IA2 to IB1 cervical cancer was performed. Subgroup analysis was performed to define a group of patients at the lowest risk for parametrial invasion based on LEEP findings. Results: Overall, 7 (5.3%) of 131 patients showed parametrial involvement, all of whom had residual tumors in hysterectomy specimens. Risk factors for residual disease included a tumor width greater than 30 mm and a positive endocervical or deep resection margin. A subgroup analysis demonstrated that LEEP parameters, including a depth of invasion of 5 mm or less and a negative endocervical resection margin, were able to define the subgroup of patients at low risk for parametrial invasion. In 24 patients (18.3%) who met these criteria, there was no evidence of parametrial spread as well as nodal metastasis. Conclusion: A subgroup of patients with early-stage cervical cancer selected by the 2 LEEP variables, depth of invasion of 5 mm or less and a negative endocervical resection margin, demonstrated no risk for parametrial invasion.